1993
DOI: 10.1136/gut.34.6.748
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Helicobacter pylori colonisation on gastric mucosal eicosanoid synthesis in patients taking non-steroidal anti-inflammatory drugs.

Abstract: Colonisation with Helicobacter pylori may influence susceptibility to gastroduodenal injury and ulceration in patients taking nonsteroidal anti-inflammatory drugs (NSAIDs). The aim of this study was to determine if Helicobacter pylori colonisation altered eicosanoid synthesis by gastric musoca in these patients. Sixty five patients with longstanding NSAID intake and 23 control subjects underwent endoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
1
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(68 citation statements)
references
References 22 publications
4
62
1
1
Order By: Relevance
“…Prostaglandin suppression leads to decreases in epithelial mucus, bicarbonate secretion, mucosal perfusion, epithelial proliferation, and mucosal resistance to injury [30,49]. Although H pylori infection stimulates mucosal prostaglandin synthesis and could theoretically provide some protection against NSAID-induced ulcers [50][51][52], evidence to support this hypothesis is lacking [53,54]. Recent data suggest H pylori infection may intensify NSAID gastrotoxicity [55,56].…”
Section: Nsaid Ulcersmentioning
confidence: 98%
“…Prostaglandin suppression leads to decreases in epithelial mucus, bicarbonate secretion, mucosal perfusion, epithelial proliferation, and mucosal resistance to injury [30,49]. Although H pylori infection stimulates mucosal prostaglandin synthesis and could theoretically provide some protection against NSAID-induced ulcers [50][51][52], evidence to support this hypothesis is lacking [53,54]. Recent data suggest H pylori infection may intensify NSAID gastrotoxicity [55,56].…”
Section: Nsaid Ulcersmentioning
confidence: 98%
“…3) Gridley et al [47] and Thun et al [48] indicated that nonsteroidal anti-inflammatory drugs (NSAIDs) may protect patients against gastric cancer as well as colorectal cancer. Wang et al [49] reported that NSAID use has been associated with a reduced risk of gastric cancer and speculated that it is possible that NSAIDs may inhibit the replication and proliferation of H. pylori [49,50], while Takahashi et al [51] and Hudson et al [52] reported that NSAIDs may neutralize the increased cyclooxygenase-2 (COX-2) expression and prostaglandin synthesis associated with H. pylori infection, thereby reducing the risk of gastric cancer. However, these drugs may also cause peptic ulcers [53], so that long-term NSAID use may be associated with an increased risk of gastroduodenal ulcer and a reduced risk of gastric cancer, but there are some negative opinions about this association [54,55], and so there is no consensus regarding the anticancer effects of NSAIDs.…”
Section: Frequencies Of Duodenal Ulcer and Gastric Cancermentioning
confidence: 99%
“…NSAID-induced gastropathy associated with the long-term use of NSAIDs is characterized by minimal mucosal inflammation, whereas H. pylori gastropathy is associated with marked mucosal neutrophilic infiltration. 15 It seems that, even in longterm NSAID users who have no history of ulcers, local mucosal factors may also be impaired and may be more important than the status of H. pylori infection in determining the development of ulcers. Although testing for the presence of H. pylori before starting NSAID therapy may be beneficial in preventing the development of NSAID-associated ulcers, this strategy is unlikely to affect the outcome in patients already taking long-term NSAIDs.…”
Section: Discussionmentioning
confidence: 99%
“…16 This may be related to the finding that mucosal prostaglandin levels are significantly decreased in NSAID users who are H. pylori negative than in patients who are infected with H. pylori. 15 However, the clinical significance of these abnormalities remains uncertain, and it is unclear whether these lesions would predict the development of true ulcers. Our study involved patients already taking continuous long-term NSAIDs (> 3 months) with no history of ulcers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation